2014
DOI: 10.5740/jaoacint.sgemanger
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric-Membrane Potential Detection of Sodium Channel Active Marine Toxins: Application to Ciguatoxins in Fish Muscle and Feasibility of Automating Saxitoxin Detection

Abstract: Ciguatoxins are potent neurotoxins with a significant public health impact. Cytotoxicity assays have allowed the most sensitive means of detection of ciguatoxin-like activity without reliance on mouse bioassays and have been invaluable in studying outbreaks. An improvement of these cell-based assays is presented here in which rapid flow cytometric detection of ciguatoxins and saxitoxins is demonstrated using fluorescent voltage sensitive dyes. A depolarization response can be detected directly due to ciguatoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…5, it could be concluded that STX could significantly reduce the beating rate (P < 0.05, n = 6) in the concentration range (0.0007-1.62 M), while STX had no significant difference (P > 0.05, n = 6) in cell index and amplitude, which indicated that the beating rate of the biosensors was a sensitive parameter to STX. The results from our experiments correlated well with previous findings reported by other investigations, where different types of function-based assays were used [18,33,34].…”
Section: Assessment Of Stx and Ttx By The Cardiomyocyte-based Biosensorsupporting
confidence: 94%
“…5, it could be concluded that STX could significantly reduce the beating rate (P < 0.05, n = 6) in the concentration range (0.0007-1.62 M), while STX had no significant difference (P > 0.05, n = 6) in cell index and amplitude, which indicated that the beating rate of the biosensors was a sensitive parameter to STX. The results from our experiments correlated well with previous findings reported by other investigations, where different types of function-based assays were used [18,33,34].…”
Section: Assessment Of Stx and Ttx By The Cardiomyocyte-based Biosensorsupporting
confidence: 94%
“…This approach is promising as depolarization can be observed in minutes versus the overnight incubations typically used for the viability end point of the N2A-MTT assays. Flow cytometric detection (Manger et al, 2014) allows selection of the most responsive cells using electronic gating. Assays based on voltage-sensitive dyes (including N2A-Flow) have not been optimized or practised by other laboratories to the same extent as the N2A-MTT format, with the latter used extensively and refined over the past 25 years.…”
Section: N2a-mtt Assay For Ciguatoxinsmentioning
confidence: 99%
“…However, with further experience in the method and with routine protocols in place for passaging the assay cells there could still be potential for further developments in this area, whilst the assay certainly remains an effective research tool. New flow cytometric assays using N2As in combination with voltage sensitive dyes are more rapid than the cytotoxicity assay, and respond to brevetoxins [ 105 ] but have not been applied to detecting brevetoxins in shellfish extracts. Similarly, a new fluorescence microscopy method involving the use of an alternative cell line to N2A cells, was developed for the assessment of cytotoxicity.…”
Section: Toxin Testing Methodsmentioning
confidence: 99%